2016
DOI: 10.1080/13880209.2016.1233569
|View full text |Cite
|
Sign up to set email alerts
|

The healing effect of Pistacia lentiscus fruit oil on laser burn

Abstract: Context: Since antiquity, Pistacia lentiscus L. (Anacardiaceae) fruit oil (PLFO) has been used as a remedy for primary health care such as burn treatment.Objective: This study assesses the healing effect of PLFO on CO2 laser fractional burn in a rat model.Materials and methods: The study was carried out on 18 adult male Wistar rats. A second-degree laser burn (wound area = 2.2 cm2) was inflicted in the dorsal region by the application of CO2 fractional laser within the following parameters; Energy level: 25 MJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
2
27
0
1
Order By: Relevance
“…In fact, MeTHF lipid extract was mainly composed by oleic and linoleic acid (47.48 and 24.12%, respectively). These two unsaturated fatty acids have anti-inflammatory properties playing a major role in the recruitment of inflammatory cells at the inflammation site (Ben Khedir et al, 2017).…”
Section: In Vitro Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, MeTHF lipid extract was mainly composed by oleic and linoleic acid (47.48 and 24.12%, respectively). These two unsaturated fatty acids have anti-inflammatory properties playing a major role in the recruitment of inflammatory cells at the inflammation site (Ben Khedir et al, 2017).…”
Section: In Vitro Anti-inflammatory Activitymentioning
confidence: 99%
“…This edible oil has been used traditionally by Tunisians in their daily diet as condiment, in salads and pastries (Trabelsi et al, 2012). The Pistacia lentiscus fruit is used as a source of medicinal oil for the treatment of many diseases such as scabies, respiratory allergies and rheumatism and also for the fabrication of antidiarrhea pills (Ben Khedir et al, 2017). Recently, several studies have reported the pharmacological virtues of this fixed oil (Mezni et al, 2016;Naouar et al, 2016;Ben Khedir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning yield values obtained on a pilot scale (0.30%), the cost of the manufacturing process of the supercritical extract weas between 999.63 USD/kg and 813.95 USD/kg. These values are considered very high when compared to the costs of other vegetable raw materials such as rosemary extract which is worth 49.71 USD/kg [21], ginger oleoresin which costs 99.80 USD/kg [20], Curcuma longa L. extract which is worth 164.4 USD/kg [40] and habanero pepper extract with a cost of 540.19 USD/kg [33].…”
Section: Cost Estimation Of Processes and Scale-upmentioning
confidence: 99%
“…In Tunisia, a species of plant called Pistacia lentiscus L., commonly known as "Dharw" in the Maghreb and "Elustaka" in the Middle East, has medicinal properties in its oil extract. The extracted oil has numerous medicianal properties, for instance anti-atherogenic [2], anti-inflammatory [3][4][5], anti-oxidant [6][7][8][9][10], antimicrobial [9,[11][12][13], hypotensive [14,15], anticancer [5,16], anti-arthritis [17], wound treatment, and anti-asthmatic and anthelmintic activities [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effect of Nigella sativa seed oil on burn wound healing process also was proven [ 13 ]. Furthermore, Khedir et al (2016) observed that Pistacia lentiscus fruit oil accelerated wound contraction in CO 2 laser burned wound model [ 14 ]. These findings consolidate the idea using the vegetable and vegetable oils for treating burn wound.…”
Section: Introductionmentioning
confidence: 99%